2000
DOI: 10.1108/08876040010327220
|View full text |Cite
|
Sign up to set email alerts
|

The determinants of perceived service quality and its relationship with satisfaction

Abstract: Deals with three issues in the area of perceived service quality. First, it compares the gap model with the performance model. Second, it investigates the direction of causality between service quality and satisfaction. Finally, it examines whether the influences of some dimensions of service quality vary across service industry types. Three service firms were selected and respondents were interviewed in each firm. As hypothesized, the performance model appeared to be superior to the gap model. In addition, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
332
2
37

Year Published

2004
2004
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 563 publications
(390 citation statements)
references
References 46 publications
19
332
2
37
Order By: Relevance
“…Parasuraman et al, (1985) suggested that when perceived service quality is high, then it will lead to increase in customer satisfaction. This supports the fact that service quality leads to customer satisfaction which is also in line with Saravana and Rao, (2007) and Lee, Lee and Yoo (2000) who acknowledged that customer satisfaction is based upon the level of service quality provided by the service provider. Lo and Huang in their study on catering industry found that causal relationship exists between service quality and customer satisfaction in the positive direction without stating whether it s weak or strong relationship.…”
Section: Service Quality and Customer Satisfactionsupporting
confidence: 70%
“…Parasuraman et al, (1985) suggested that when perceived service quality is high, then it will lead to increase in customer satisfaction. This supports the fact that service quality leads to customer satisfaction which is also in line with Saravana and Rao, (2007) and Lee, Lee and Yoo (2000) who acknowledged that customer satisfaction is based upon the level of service quality provided by the service provider. Lo and Huang in their study on catering industry found that causal relationship exists between service quality and customer satisfaction in the positive direction without stating whether it s weak or strong relationship.…”
Section: Service Quality and Customer Satisfactionsupporting
confidence: 70%
“…This technique has been widely adopted in previous research to provide insight on gaps that arise from inconsistent perceptions of expectations and experience [59][60][61]. To examine if the characteristics of the garment workers are related to their perceptions of decent work, multiple regression analysis was performed to examine the relationships.…”
Section: Discussionmentioning
confidence: 99%
“…Output of this analysis is provided by IBM SPSS v21 and indicates significantly high reliability of data (Cronin & Taylor 1992;Lee et al, 2000) and is depicted in Table 3. …”
Section: Reliability Analysismentioning
confidence: 99%